Goods produced by poor populations that with training, economic support and concessions, can no longer be poor - Barreda Guerra, Juan Manuel (2021)
We all witness the level of ethical and moral rot in the highest spheres of politics in our country, in three decades of our own and strangers robbed us of more than 70,000´000,000 million dollars, even so, the large, medium, small and micro Entrepreneur are still determined to achieve their business objectives. This year 2019, despite the enormous political crisis in which we find ourselves, we will have a slight increase in exports of the agricultural sector, the largest participation in it, will be the large and medium agricultural entrepreneurs of the Coast, depending on the amount of resources available in this natural region. On the other hand, in the natural regions of the Sierra and the jungle millions of agrarian families live together with their productions in situations of poverty and extreme poverty because they do not have similar resources, in this sense they urgently need to determine a vision of the sector setting goals of inclusion economic and, corresponding strategies and action plans of short, medium and long term on agricultural growth and development based on territorial planning with multi-resource allocation, in order to take advantage the great opportunities and the enormous productive potential of our agricultural territories in the face of countless trade agreements and markets as a result of globalization and, thus, gradually overcome extreme poverty and poverty in this sector. The objectives involve coverage of internal demand that includes state purchases with the allocation of exclusive associative suppliers and, in the same way, the generation of productions with exportable offers.